Developing a Conceptual Model on Human Resource Planning of Rural Healthcare Centers of West Bengal Based on TOE Framework : A Qualitative Study Using NVIVO - Chatterjee, Satakshi; Giri, Arunangshu; Bandyopadhyay, Soumendra Nath (Prabandhan: Indian Journal of Management, 2024)
Purpose : The objective of this short communication was to identify the factors that were responsible for this disparity between the supply and demand of healthcare professionals and its impact on perceived service quality. Design/Methodology/Approach : A qualitative research design was used to create a conceptual model in this study. Personal interviews were conducted with 43 respondents. All of these respondents were working in various administrative roles in various rural healthcare centers. These data were analyzed with the help of the software tool NVIVO 14.0. Findings : The findings demonstrated the significant influence of technological, organizational, and environmental factors on the supply and demand of healthcare professionalsâ€™ human resource planning (HRP). Additionally, the perceived quality of services was impacted by hospital HRP. Practical Implications : In the global setting, most healthcare systems struggle with a lack of clinical and non-clinical personnel; this was particularly the case in rural areas. The need for healthcare services is growing, yet there is a significant gap in the availability of medical personnel in large cities compared to rural or isolated areas. This has grown to be a major worry, and it must be given top priority attention. Originality/Value : This brief statement developed a conceptual model on the elements influencing the West Bengal Rural Healthcare Centers’ HRP process in contrast to earlier studies on HRP in the healthcare sector.